(untitled) (Fiep Bulletin - online, 2014)
Over the last decades the transformation process of the means of production composed a new social structure, which impacted in the people’s lifestyle. The new population’ profile, particularly workers, has shown increased prevalence of overweight associated with metabolic abnormalities, cardiovascular disease, among others. Such characterization can also be seen in agribusiness workers. In this perspective, this study aims to investigate the relationship between diseases self-reported by agribusiness workers and farmers, relating data of body mass index (BMI) and socioeconomic status. The methodology was based on a quantitative descriptive study, in which the subjects were 140 rural producers. Statistical analysis was performed using the Statistical Package for Social Sciences, through frequency and percentage. Among those surveyed, 62.9% were female, with a mean age of 51.04 years (SD: 10.63). There was predominance of socioeconomic class B2 (39.3%) and excess weight (87.9%). The diseases most commonly cited were Hypertension (HBP), cholesterol, gastritis, and sleep disturbance, and when relating these diseases to BMI, there is a predominance of overweight and obesity. In addition, correlating self-reported diseases with the socioeconomic, it is possible to realize that all of them are predominantly in classes B2 and C1. From these results, it was noted the importance of promoting health and especially to sensitize this population about the risks of being overweight, which most of the time lacks information and guidance on health.